2012
DOI: 10.1637/9839-062011-resnote.1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Pooling 11 or 5 Oropharyngeal Swabbings for Detecting Avian Influenza Virus by Real-Time Reverse Transcription–PCR in Broiler Chickens

Abstract: The effect of pooling 11 or 5 oropharyngeal (O/P) swabbings on detecting avian influenza virus (AIV) by real-time reverse transcription (RRT)-PCR was evaluated. The model used for the evaluation was designed to minimize viral load and, thus, assess the effect of the pooling on detection. Two-week-old broiler chickens were inoculated via the intranasal route with the low pathogenicity chicken/Maryland/Minh Ma/04 H7N2 strain or remained uninoculated. On days 2, 3, 4, 5, 7, 9, 11, and 14 postinoculation (PI), O/P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 9 publications
2
14
0
Order By: Relevance
“…On the potential effect of swab pooling, our findings for combined virus subtypes indicate that pooling up to 10 negative swabs with one positive swab reduced the viral antigen concentration and consequently the proportion of FluDETECT positive samples. This result is largely consistent with those of Ladman et al [11]. However, a study by Spackman et al [39] did not find differences in virus detection between a single swab from an inoculated bird, 5 swabs (1 from an inoculated bird, 4 from unexposed birds), or 11 swabs (1 from an inoculated bird and 10 from unexposed birds) by real time RT-PCR.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…On the potential effect of swab pooling, our findings for combined virus subtypes indicate that pooling up to 10 negative swabs with one positive swab reduced the viral antigen concentration and consequently the proportion of FluDETECT positive samples. This result is largely consistent with those of Ladman et al [11]. However, a study by Spackman et al [39] did not find differences in virus detection between a single swab from an inoculated bird, 5 swabs (1 from an inoculated bird, 4 from unexposed birds), or 11 swabs (1 from an inoculated bird and 10 from unexposed birds) by real time RT-PCR.…”
Section: Discussionsupporting
confidence: 91%
“…Its ability to detect the virus in pools of 11 was compared with that in individual pools of 5 or 6 and in combined pools of 5 or 6 for separate H5 and H7 subtypes as well as for merged H5 and H7 sample groups. Only samples with CT ≤ 35 were considered RT-PCR positive [11, 19] and in the comparison of virus positive proportions, Fisher’s exact test at significance level of p  ≤ 0.05 was used [20]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An upper limit of 11 swabs has been suggested based on the statistical calculation where 11 swabs from a flock (of 10,000 or more) should be sufficient to detect 25% infection rate with 95% confidence, which is the level of surveillance outlined by the NPIP. A previous study comparing 5 and 11 swabs for detection of LPAIV from broilers by rRT-PCR has been reported and found no difference [2]. Another study comparing a single swab with pools of 5 with samples from turkeys also found no difference [1] This study agrees with those results and adds a comparison with single swabs, five and 11 swab pools in one experiment and very importantly, data for VI.…”
Section: Discussionsupporting
confidence: 84%
“…Evaluations of swab pooling for AIV using only real-time (rRT-PCR), but not virus isolation have been reported [1,2]. Similarly, detection of AIV with wet versus dry swabs from Pekin ducks tested by rRT-PCR only has been compared [3].…”
Section: Introductionmentioning
confidence: 99%